202 PREMENSTRUAL SYNDROME AND NEGATIVE MOODS IN COLLEGE-AGED WOMEN. Issue 1 (1st January 2007) - Abejuela, H. R.; Roberts, S.; Stuber, M.
Abstract : Purpose: Studies have demonstrated that over 80% of women have premenstrual syndrome (PMS) and that PMS is associated with numerous physical and mood changes. Irritability appears to be the most prevalent negative mood associated with PMS in women aged 28 to 45 years old. However, little is known about prevalent negative moods associated with PMS in college-aged women. Methods: Eight undergraduate students from the University of California at Berkeley aged between 18 and 22 years old were given a diary and calendar to rate their daily moods on a numerical scale of 1 to 7 (1 for lowest mood, 4 for baseline of normal mood for each participant, and 7 for highest mood) over three menstrual cycles. Participants were required to (1) rate their moods, (2) indicate their top three negative moods selected from a compiled list of commonly reported PMS-associated negative moods, and (3) record their number of hours of sleep on a daily basis. Statistical analyses were performed using the SPSS 11.0 statistical software package. Results: The lowest moods were reported during the premenstrual phases (92%), whereas higher moods were apparent during the postmenstrual phases. Counter to previous studies, the most prevalent negative moods during the premenstrual phases were "sadness" and "feelings of worthlessness" (reported by 5 of 8 participants) rather than "irritability." The number of hours of sleep was weakly correlated with mood during the premenstrual phases ( r = .23, p = .032) but not during the postmenstrual phases. Conclusion: PMS-related mood symptoms may be different in college-aged women than in older women. Given that "sadness" and "feelings of worthlessness" are clinically related to depression and/or suicidal ideation, measures to prevent and/or better control these PMS-related mood changes among affected college-aged populations should be explored.